Optimisation of floor evacuation map based on drive design. - Liao, Huimin; Zheng, Kexin; Yi, Jiazheng (Ergonomics, 2025)
To investigate the optimisation scheme for a floor evacuation map, library, and mall scenarios were considered as examples, and drive designs, including non-drive design, salient stimulus-drive design, and working memory-drive design, were introduced in the experiment. Participants' wayfinding behaviour and responses were studied by analysing the average duration of fixation (ADF), average fixation counts (AFC), accuracy rate (AR), response time (RT), and other relevant indices. The experimental data revealed that both the salient stimulus-drive and working memory-drive designs significantly reduced the ADF and AFC compared to the non-drive design while improving the AR. The RT of the salient stimulus-driven group was significantly longer than that of the other two groups. The experimental results indicated that incorporating floor plans and relevant salient stimuli into the design of floor evacuation maps can enhance their readability, thereby facilitating better retention of evacuation routes by participants. Practitioner Summary: This study aimed to use stimulus-driven design and the working memory-drive design to optimise floor evacuation maps. Task performance and eye movement results indicated that these two designs significantly improved participants' performance in the exit search process. The optimisation scheme was proposed based on these findings.